Determinants of Competitive Advantage and its Implications for MSME Business Performance - Sulaiman, Anwar (AGUSPATI Research Institute, 2024)
The purpose of this study was to analyze the effect of e-CRM, and customer involvement capability onbusiness performance with competitive advantage as an intervening variable. The method used isquantitative method, with a total of 200 respondents. Data analysis using SEM Lisrel 8.80 Based onthe research results, the following research findings were obtained e-CRM has a positive andsignificant effect on competitive advantage, customer involvement capability has a positive andsignificant effect on competitive advantage, e-CRM has a positive and significant effect on businessperformance, customer involvement capability has a positive and significant effect on businessperformance competitive advantage has a positive and significant effect on business performance. eCRM, customer involvement capability and competitive advantage simultaneously have a positive andsignificant effect on the business performance of MSMEs in Bogor Regency